2023
DOI: 10.1002/app.53913
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of properties and aging resistance of epoxy asphalt composite modified by ultraviolet absorber

Abstract: This research investigated the effect of ultraviolet absorber (UV‐531) on the properties of epoxy asphalt (EA) binders. EA binders were modified by adding UV‐531 absorber at contents of 0, 0.3, 0.6, 0.9, and 1.2 wt%, and composites were then subjected to ultraviolet (UV)‐based aging, including UV, oxygen, and heat treatment. Laboratory tests were conducted to assess UV absorption, viscosity, mechanical parameters, contact angle, microstructure, and chemical functional groups of absorber‐modified EA composites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…LSMs primarily reflect and shield ultraviolet radiation, reducing the damage of ultraviolet rays to functional groups and chemical bonds of asphalt . LAMs absorb the energy of ultraviolet radiation and convert it into low-energy heat, reducing the direct damage of ultraviolet energy to asphalt . AOMs react with active free radicals in asphalt, stabilizing them and slowing down the chain reaction process of active free radicals in asphalt .…”
Section: Introductionmentioning
confidence: 99%
“…LSMs primarily reflect and shield ultraviolet radiation, reducing the damage of ultraviolet rays to functional groups and chemical bonds of asphalt . LAMs absorb the energy of ultraviolet radiation and convert it into low-energy heat, reducing the direct damage of ultraviolet energy to asphalt . AOMs react with active free radicals in asphalt, stabilizing them and slowing down the chain reaction process of active free radicals in asphalt .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The chemical components of EA undergo changes during photooxidation aging, which affects its mechanical properties. [12][13][14] The mechanical properties of EA depend on the cross-linking network of epoxy resin, as the modulus of epoxy resin is much higher than that of asphalt. 15 Different molecular segments were introduced into the epoxy resin cross-linking network to adjust the mechanical properties of EA by changing the type and ratio of curing agents.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the effective content of old asphalt, some researchers have suggested that the mechanical properties of fused asphalt lie between those of old and new asphalt binders, making mechanical characteristics suitable measures for the DoB 13,14 . However, due to the thermosetting nature of epoxy asphalt, it is difficult to extract cured epoxy asphalt from the surface of aggregates for performance testing 15 . Therefore, new characterizing methods are needed to evaluate the blending between new and old asphalt in HMA containing both RAP and epoxy asphalt (hereinafter referred to as “epoxy‐modified hot recycled asphalt mixture”).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However, due to the thermosetting nature of epoxy asphalt, it is difficult to extract cured epoxy asphalt from the surface of aggregates for performance testing. 15 Therefore, new characterizing methods are needed to evaluate the blending between new and old asphalt in HMA containing both RAP and epoxy asphalt (hereinafter referred to as "epoxy-modified hot recycled asphalt mixture").…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation